Трансформація висвітлення військової тематики українськими ЗМІ на прикладі телеканалів «1+1» та «Інтер» з початку повномасштабної війни - Ціхоцький, Іван Михайлович; Tsikhotskyi, Ivan Mykhailovych (Національний університет "Львівська політехніка", 2024)
Мета бакалаврської роботи – дослідити трансформації висвітлення військової тематики українськими ЗМІ на прикладі телеканалів «1+1» та «Інтер» з початку повномасштабної війни. Реалізація мети передбачає розв’язання таких завдань: визначити особливості функціонування ЗМІ в умовах війни та їхній вплив на суспільство; проаналізувати зміну редакційних підходів телеканалів «1+1» та «Інтер» щодо висвітлення воєнної тематики; провести порівняльний аналіз змістового наповнення та форматів подачі новин на зазначених телеканалах; оцінити громадське сприйняття змін у подачі військових новин на українському телебаченні. Об'єктом дослідження є українські телеканали «1+1» та «Інтер». Предмет дослідження – особливості висвітлення воєнної тематики у новинних блоках зазначених телеканалів після початку повномасштабної війни. У бакалаврській роботі проаналізовано специфіку інформаційної подачі новинного контенту воєнного характеру, особливості використання журналістських прийомів, стилістичних засобів та змістовних акцентів у висвітленні бойових дій, а також вплив інформаційної політики телеканалів на сприйняття глядачами воєнної реальності. Робота включає теоретичний аналіз функцій ЗМІ у період війни, порівняльне дослідження новинних випусків «1+1» та «Інтер» і результати соціологічного опитування щодо сприйняття телеглядачами воєнної тематики.

The purpose of the bachelor's thesis is to research the transformation of how Ukrainian media cover military topics, using the television channels "1+1" and "Inter" as examples since the beginning of the full-scale war. Achieving this aim involves solving the following tasks: identifying the specifics of media functioning during wartime and their impact on society; analyzing changes in the editorial approaches of the "1+1" and "Inter" channels regarding the coverage of military topics; conducting a comparative analysis of the content and news presentation formats on the aforementioned channels; evaluating public perception of changes in the presentation of military news on Ukrainian television. The object of the research is the Ukrainian TV channels "1+1" and "Inter." The subject of the research is the peculiarities of covering military topics in the news segments of these channels after the onset of the full-scale war. The bachelor's thesis analyzes the specifics of how war-related news content is presented, the use of journalistic techniques, stylistic tools, and thematic emphases in covering military actions, as well as the impact of the TV channels' information policies on viewers' perception of war realities. The work includes a theoretical analysis of the media's functions during wartime, a comparative study of news broadcasts on "1+1" and "Inter," and the results of a sociological survey on how viewers perceive military content on television. Key words: military topics, news, television, "1+1" TV channel, "Inter" TV channel, mass media, information policy, public opinion, journalistic standards, full-scale war.
The transformation of coverage of military topics by the Ukrainian mass media on the example of the TV channels «1+1» and «Inter» since the beginning of the full-scale war
Keywords: 6.061.00.00; воєнна тематика; новини; телебачення; телеканал «1+1»; телеканал «Інтер»; мас-медіа; інформаційна політика; громадська думка; журналістські стандарти; повномасштабна війна